2019
DOI: 10.3390/ijerph16142528
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Dental Treatment under General Anaesthesia in Medically Compromised and Healthy Children

Abstract: Dental care under general anaesthesia (GA) is an option when normal treatment cannot be accomplished due to un-cooperation and systemic or cognitive/intellectual disabilities. The purpose of this retrospective cohort study was to analyse the dental treatment under GA in medically compromised and healthy children. The data were collected from the medical records of children who received their dental treatment under GA. The data regarding patient age, sex, general health, and type of treatment were analysed. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The Chi-Square non-parametric test was used to determine if there was a relationship between two variables: in this case occurring DH symptoms and suffering from cGvHD. We used the Mann-Whitney test for comparing two conditions without making the assumption that values are normally distributed and the Kruskal-Wallis Test for comparing more than two groups [32,33]. For all the calculations, statistical significance was set at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The Chi-Square non-parametric test was used to determine if there was a relationship between two variables: in this case occurring DH symptoms and suffering from cGvHD. We used the Mann-Whitney test for comparing two conditions without making the assumption that values are normally distributed and the Kruskal-Wallis Test for comparing more than two groups [32,33]. For all the calculations, statistical significance was set at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…When creating an official protocol, a meticulous methodology should be used in order to cover all complex aspects of indications for dental treatment in persons with ID under GA. Since no protocol exists, dental practitioners in specialized institutions are left with tough decisions regarding indications for dental treatments under GA. As previously reported, dental procedures in GA for adults with ID are more radical, since multi-visit procedures are omitted, advanced caries therapy in terms of pulp medication are limited due to uncontrollable outcomes, and options for orthodontic and prosthodontics rehabilitation are extremely reduced (Koberova Ivancakova, Suchanek, Kovacsova, Cermakova, & Merglova, 2019). Consequently, dental treatment in persons with ID under GA usually leads to multiple teeth extractions, causing additional functional and aesthetic problems, the need for prosthodontic rehabilitation, and a negative effect on almost all aspects of everyday life (Oh et al, 2018;Schnabl et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Although feasible, the associated costs and technologies can limit access. 7,8 Furthermore, it has already been demonstrated that the organization of oral health services is an important factor in the use of these resources and technologies for patients with complex disabilities requiring dental treatments. 9 Apart from systemic health problems, cariesrelated hospital admissions may reflect Public Health problems, such as negligence, socioeconomic disparities in access to oral health services, and the need for advanced treatments for oral diseases that can be managed and prevented by the Primary Health Care setting (outpatient level).…”
Section: Introductionmentioning
confidence: 99%